An approach to heart failure for the public-sector primary care clinician - Liezel Rossouw; Anthony S. Lachman; Klaus B. von Pressentin (South African Family Practice, 2025)
Heart failure poses a significant global health challenge, with a considerable burden in Africa, where the annual mortality rate stands at 34%, twice the global average. Patients suffering from acute heart failure occupy numerous beds at the district level, and only a limited number can be referred for further evaluation and imaging at secondary or tertiary care facilities. Patients rely on their primary care physicians for the diagnosis and management of heart failure, as well as for identifying those who would benefit from referral to cardiology and formal echocardiography. This article discusses the significance of the new heart failure guidelines within the South African primary care public setting. It emphasises the importance of identifying risk factors and considers the value of access to family physicians, outreach clinic doctors, training on available adult primary care guidelines and telemedicine-supported cardiac ultrasound. Optimal medical therapy, which includes angiotensin-converting enzyme (ACE) inhibitors, beta-blockers and spironolactone, has been shown to reduce readmissions and mortality rates. Sodium-glucose cotransporter-2 (SGLT2) inhibitors are a potent addition to conventional therapy and are currently being considered for inclusion in the National Essential Medicines List. Patients admitted to the hospital should not be discharged while experiencing persistent congestion, as this is associated with an increased risk of rehospitalisation, mortality and higher healthcare costs. Comprehensive patient education regarding medications, thorough follow-up during the six weeks post-discharge and linkage to primary healthcare are associated with decreased hospitalisation rates and improved outcomes.